Types of consent in reproductive health care. Issue 2 (February 2015) - Dickens, Bernard M.; Cook, Rebecca J.
Abstract: Healthcare providers require prior consent to treat patients. Consent can be different for legal purposes, and be expressed in different ways. Simple consent affords providers protection from liability for assault, but negligence can arise if the consent is inadequately informed. Providers cannot coerce or improperly induce consent; patients' agreement that a provider wrongly influences is compliance, not true consent. Attempts to rescue patients in peril may be lawful on the presumption of their implied consent, unless patients negate the presumption. In special cases, laws may require that consent be written, but generally consent can be given by speech or conduct. Informed consent depends on patients' comprehension, but consent for treatment of uncomprehending patients may come from third parties, including legally recognized substitutes or judges. There may be legal limits to reproductive procedures to which patients may consent, under laws that can be respectfully tested, but have to be obeyed.